The Effect of Emergency Management Skills Training for Nurses - Fitriani, Rani; Buka, Sisilia Prima Yanuaria; Niva, Matteson; Maharjan, Kailie; Xavier, Embrechts (Yayasan Pendidikan Islam Daarut Thufulah, 2024)
The role of nurses in emergency management is very crucial in providing effective and timely services to patients. Training in emergency management skills is important to improve nurses' competence in situations that require a quick and precise response. The aim of this research is to evaluate the effect of emergency management skills training for nurses on increasing competence and readiness in responding to emergency situations. This research method uses a pre-test post-test study design with a control group, where a number of nurses from various care units are identified and divided into an intervention group (which received training) and a control group (without training). Training is carried out using simulation methods and practical exercises involving realistic emergency scenarios. Before and after training, both groups were tested to measure their level of competency and readiness in responding to emergency situations. The results of the study showed a significant increase in the level of competency and readiness to respond to emergency situations in the group that received emergency handling skills training compared to the control group. Nurses who undergo training show increased abilities in evaluating situations, making decisions, and implementing appropriate actions in emergency situations. The conclusion of this research is that training in emergency management skills has a significant positive influence on increasing the competency and readiness of nurses in responding to emergency situations. Implementing regular and comprehensive training in care environments can be an effective strategy for improving healthcare standards and patient safety.